Batch public auditing for distributed mobile cloud computing. (2015) - Yao, Chuan; Xu, Li; Huang, Xinyi
Mobile cloud computing (MCC) has been envisioned as the major service participants nowadays. In addition to the classic security and privacy concerns, outsourcing data in MCC requires special attention since mobile devices are of low power and the network condition varies. Therefore, an efficient, secure and robust data storage mechanism is necessary. This paper presents an efficient data encryption protocol for distributed mobile systems such as MCC. Our new protocol contains several desirable properties, including improved system robustness, batch and public audit, collusion preventing, and open channel transmission. With the proposed protocol, users in MCC can securely outsource data to the cloud in an efficient way.